Effects of matrix composition and surface treatment on the bond strength of glass fiber-reinforced composite posts to root dentin - Melika Hoseinzadeh; Ehsan Baradaran Naseri; Mohammad Javad Moghaddas; Navid Kerayechian; Sajjad Mosafer (Journal of Dental Materials and Techniques)
Objective: This study evaluated the effects of resin matrix composition and surface treatment on the bond strength of glass fiber-reinforced composite (FRC) posts to intraradicular dentin.Methods: Fifty-six extracted premolars were obtained. Post spaces were prepared for either epoxy resin-based posts (White Post DC) or Bis-GMA-based posts (Postec Plus) (n=28). The posts received different surface treatments (n=7): 70% ethanol (control), air abrasion and silanization, 35% H3PO4, and 24% H2O2. Posts were cemented and the samples were sectioned into cervical, middle, and apical thirds. The push-out bond strength of samples was compared between the groups using two-way ANOVA (α=0.05).Results: There was a significant difference in bond strength between the different treatment methods in all root sections (P < 0.05). The highest push-out bond strength in the cervical, middle, and apical sections was observed in subgroups treated with air abrasion and silanization, with a significant difference from other groups in most comparisons (P < 0.05). Epoxy resin and Bis-GMA posts had comparable bond strengths in the coronal and apical sections (P > 0.05). Additionally, their bond strengths were comparable in the middle section when the post surfaces were treated with air abrasion and silanization, or 35% H₃PO₄ (P > 0.05).Conclusions: Air abrasion and silanization could be suggested as the optimal surface treatment strategy to improve the bond strength of FRC posts to resin cement. Proper mechanical and chemical surface treatments might be more important than the resin matrix composition in determining the bond strength of FRC posts.